Cocrystallization‐Induced Spontaneous Deracemization: A General Thermodynamic Approach to Deracemization. (6th April 2020) - Guillot, Michael; de Meester, Joséphine; Huynen, Sarah; Collard, Laurent; Robeyns, Koen; Riant, Olivier; Leyssens, Tom
Abstract: Processes leading to enantiomerically pure compounds are of utmost importance, in particular for the pharmaceutical industry. Starting from a racemic mixture, crystallization‐induced diastereomeric transformation allows in theory for 100 % transformation of the desired enantiomer. However, this method has the inherent limiting requirement for the organic compound to form a salt. Herein, this limitation is lifted by introducing cocrystallization in the context of thermodynamic deracemization, with the process applied to a model chiral fungicide. We report a new general single thermodynamic deracemization process based on cocrystallization for the deracemization of ( R, S )‐4, 4‐dimethyl‐1‐(4‐fluorophenyl)‐2‐(1 H ‐1, 2, 4‐triazol‐1‐yl)pentan‐3‐one. This study demonstrates the feasibility of this novel approach and paves the way to further development of such processes. Abstract : One model to fit all : As a general approach to deracemization, cocrystallization‐induced spontaneous deracemization takes advantage of the universal dimension of cocrystallization to create a pair of diastereomers and combines it with a racemization reaction in solution (see picture). This model was successfully applied to a fungicide, the deracemization of which was not possible by established methods.